2010
DOI: 10.1002/j.2050-0416.2010.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review: The Role of Barley Seed Pathogenesis-Related Proteins (PRs) in Beer Production

Abstract: Pathogenesis-related proteins (PRs) are involved in the protection of dormant and germinating cereal seeds against pathogenic microorganisms and pests. Moreover, barley grain PRs have considerable technological importance in the brewing of beer. The compact structure of PRs allows them to survive the hostile conditions of the extracellular compartments, where they are usually localized, and enables the endurance of certain classes of PRs during the harsh conditions of the technological steps of beer production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 136 publications
0
19
0
2
Order By: Relevance
“…Alongside hydrophobins, the well-known gushing inducers fungispumins [17,18], as well as elevated levels of pathogenesis-related proteins (PRs), might be responsible for gushing [18].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside hydrophobins, the well-known gushing inducers fungispumins [17,18], as well as elevated levels of pathogenesis-related proteins (PRs), might be responsible for gushing [18].…”
Section: Introductionmentioning
confidence: 99%
“…The protein composition of malt, which is obtained from germinated and heated or roasted barley, and beer changes during the beer production process, which includes malting, mashing, boiling, fermentation and filtering. Protein Z is one of the most abundant malt and beer proteins,and is also present in barley . Protein Z is highly stable and is able to resist denaturation during the harsh treatment steps from malting to brewing.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protein Z, LTP1 is another major beer protein. Both proteins are pathogenesis‐related proteins and are potentially common human food allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Stanislava [50] reported that thaumatin-like protein (TLP) and ns-LTP1 purified to homogeneity from malting barley inhibited brewer's yeast growth, fermentation and respiration. Aging yeast cells from a brewery were more susceptible to these factors than the same yeast strain propagated in the laboratory.…”
Section: Antimicrobial Peptide Hypothesis Of Pyfmentioning
confidence: 99%